(untitled) (The Pakistan Development Review, 1995)
An important component of human capital formation is improvements in the health status of the population.1 Improvements in the health status of a nation can lead to longer life expectancy, shift the labour supply curve outward, increase labour productivity, and increase the productivity of investment in other forms of human capital, particularly education. Since health and the capacity to improve health are related to socio-economic conditions, it is important to analyse the impact of changes in these variables on the provision of health services. Due to the presence of externalities, market failures, and inability of a significant proportion of the population to pay, government intervention is required in the health sector. In this study, we shall analyse the changes in the provision of public health resources in Pakistan, in response to the changes in socio-economic factors. Most empirical studies in this area have been cross-country studies. Fulop and Reinke (1983) emphasise that socio-economic factors affect the health status directly and indirectly. The indirect effect is through the changes in health resources in response to the changes in socio-economic factors. Kleiman’s (1986) cross-country analysis shows that per capita national income, the ratio of government consumption expenditure to private consumption expenditure, and the measure of income inequality are important determinants of public expenditure on health. The study also shows that public and private expenditure on health are good if not a perfect substitute for each other.